The sustainability of the construction industry in sub-saharan Africa: some new evidence from recent data - Lopes, Jorge (2018)
The relationship between a country’s level of construction activity and its stage of economic development has been the subject of study at the macroeconomic level for a number of years. The dominant paradigm in the field is that the construction industry follows an inverted U shaped development pattern i.e. the share of construction in national economy first increases in the early stages of development and ultimately decline in the latest stages of development. An examination of construction indicators in two categories of countries in Sub-Saharan Africa is made and the link between construction investment and the economic and social targets of the sustainable development goals is considered.